Over-utilization of computed tomography angiography in extremity trauma. Issue 4 (December 2019) - Callan, Alexandra K.; Bauer, Jennifer M.; Mir, Hassan R.
Abstract: Objectives: Widespread availability of computed tomography angiography (CTA) for diagnosing arterial injury in injured extremities has created the possibility of overuse. The objective of this study was to evaluate CTA utilization, indications, ordering personnel, and rate of significant findings for blunt or penetrating extremity trauma at a level I trauma center. Methods: We performed a retrospective chart review of 1440 consecutive CTAs of upper and lower extremities from 2010 to 2012 at a large level I trauma center, and included only those done for acute trauma. Data were collected with regard to injury, initial exam, reason given for ordering a CTA, specialty of physician ordering CTA, results, and vascular interventions needed. CTAs were categorized as appropriately ordered based on if there was a documented abnormal distal pulse or ankle-brachial index (ABI). Study indication was classified as inconclusive if no vascular exam was documented or physical exam varied. Results: A total of 481 CTAs were performed after blunt or penetrating trauma in the emergency room with 31.0% appropriately indicated, 48.0% without indication, and 21.8% inconclusive. Mechanism of injury was most commonly a gunshot wound (40.3%), followed by motor vehicle accidents (39.5%). Overall, 61.5% of the studies had normal arterial flow and only 15.8% of CTAs required vascular operative intervention. Of the studies appropriately indicated, 76.5% had positive findings, with 43% needing operative intervention compared to the inappropriately indicated studies only 11.6% had positive findings, with 0.4% needing operative intervention ( P <  .0001). Conclusion: CTA for blunt or penetrating trauma at a level I trauma center may be over-utilized. Often, this advanced imaging is ordered prior to orthopaedic evaluation or limb reduction, without exam-based indication, and most do not affect patients' treatment. From our study, CTA utilization based on more stringent exam findings at our hospital could eliminate 48% of all CTA studies for trauma.